PERANAN INTEGRITAS DAN KOMITMEN ORGANISASI TERHADAP KINERJA - M Sandi Prasetyo; Siska Adinda Prabowo Putri (IMAGE, 2023)
This research aims to empirically test the relationship between integrity and organizational commitment to performance. The sample used was 108 members of the Ditreskrimsus Polda Jateng. The sampling technique used is simple random sampling. The analysis used is multiple regression analysis. This employee performance variable is measured using the Individual Working Performance (IWPQ) scale from Koopmans. The integrity variable is measured using a Likert scale which is based on Rogers' theory of integrity aspects, including honesty, steadfastness, self-control and self-esteem. The organizational commitment variable is also measured using a Likert scale based on Allen & Meyer's theory of affective commitment, rational commitment and normative commitment. Based on the research results, the first result was obtained; There is a correlation between integrity and organizational commitment to performance. Second; Integrity does not affect performance. Third; Organizational commitment has a positive and very significant effect on performance. The coefficient of determination value in this research is shown by the value R2 = 0.132 or 13.2%, which means that integrity and organizational commitment influence performance by 13.2% and the remaining 86.8% is influenced by other factors. Keywords: Performance, Integrity, Organizational Commitment